Fa`āliyah Taṭbīq Uslūb Teams Games Tournament Bi Kahoot Wa aṭ-Ṭarīqah al-Qiyāsiyyah Bi al-Biṭṭāqah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā al-Qawā`id An-Naḥwiyyah (Dirāsah Tajrībiyyah Bi al-Āmiliyah Bi Ma`had al-Furqān) - Alvia Rahmi; Ahmad Fauzi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
As stated by students through the interview they acknowledged the difficulties in learning Arabic such as Qawa'id. Students found difficulty with the use of Isim Dhomir and the difference of Fi'il (verb) as well as the use of Jar and Mubtada Khabar letters while learning Qawa'id. Besides, they also found difficulty in formulating the correct sentences according to Qawaid rules. Based on the experience of the teacher, students’ ability is very lack in mastering the Qawa'id materials. It is shown by the result of the Qawa'id assignments given. Furthermore, the students did not remember what the teacher explained when they were asked back by the teacher. The teacher points out that the students lack the motivation to learn Arabic. This problem will affect students' ability to accept the material. The purpose of this study was to (1) determine the effectiveness of the Teams Games Tournament model with Kahoot to improve students' ability to Qawa'id Nahwiyyah. (2) to determine the effectiveness of the Teams Games Tournament model with Kahoot to improve students' ability to Qawa'id Nahwiyyah. (3) Determine the effectiveness of the Qiyasiyyah method with cards to improve students' ability to Qawa'id Nahwiyyah. (4) Knowing the effectiveness of the Qiyasiyyah method with cards to improve students' ability to Qawa'id Nahwiyyah. The research methodology in this thesis is an experimental method with a factorial design (The 2 x 2 Factorial Design). Based on the explanation, the researcher concluded that (1) The application of the team's games tournament model with Kahoot was effective in improving the ability of students (lk) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the signification level of 0.000 ≤ 0.05. (2) Implementation of the team's games tournament model with Kahoot is not effective in improving the ability of students (pr) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the signification level of 0.065 > 0.05. (3) Application of the Qiyasiyyah method with cards effectively to improve the ability of students (lk) to Qawaid Nahwiyyah. With evidence that the distribution of data is at the signification level of 0.015 ≤ 0.05. (4) Application of the Qiyasiyyah method with cards effective to improve the ability of students (pr) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the signification level of 0.004 ≤ 0.05.